The current state of implementation of the public-private partnership project in the field of health - Барлыков, Е. (Journal of Economic Research & Business Administration, 2017)
The article examined the current state of implementation of the public-private partnership project in the field of public health. The relevance of the article is to create an infrastructure that meets the demand for affordable and quality services for the further implementation of health reforms. Also, the application of public-private partnership is necessary in the implementation of social programs. Services in the field of infrastructure and public needs that are compatible with budgetary and financial constraints require the implementation of many socio-economic projects. In this case, it will be relevant to search for new forms of state regulation and the impact on the economy directly from alternative ways. The article considers the years of construction of public health facilities, the structure of health facilities, major public-private projects in the field of health. The Ministry of Health of the Republic of Kazakhstan plans to implement projects within the concession agreement in accordance with the contract system of public-private partnership. This means that the implementation of concession projects on behalf of the State of the Ministry of Health of the Republic of Kazakhstan and the subject of private partnership and cooperation will contribute to the development of the healthcare, medical education and medical science. Therefore, these projects are aimed at financing, building and using the facility for the creation of social infrastructure and life support. Based on the reviewed projects, the Grantor becomes the organizer of the tender for the choice of the Concessionaire, and concludes the concession contract. The concessionaire constructs the concession object and issues it into state ownership.